Epidemiology of eye injuries in childhood - E. N. Eskina (Oftalʹmologiâ, 2015)
Summary: eye injuries are one of the leading causes of blindness and low vision at any age. The article provides an overview of the literature on the frequency, reasons and epidemiology of eye injuries in children. The results of the survey showed that boys aged 5‑7 years old are most susceptible to trauma of the eye and its appendages at home or on the street with no adult supervision. High level of injuries and monocular blindness due to them requires intensive study of this problem with the development and implementation of effective preventive measures.